2015
DOI: 10.1039/c4lc01248h
|View full text |Cite
|
Sign up to set email alerts
|

A siphonage flow and thread-based low-cost platform enables quantitative and sensitive assays

Abstract: For pump-free, material abundant, portable, and easy-to-operate low-cost microfluidics, a siphonage flow microfluidic thread-based analytical device (S-μTAD) platform enabling quantitative and sensitive assays was designed. Renewable and continuous siphonage flow allowed replicate sampling and detection on one channel/device, obviating some possible inconsistencies among channels or devices. Y-shaped channels were fabricated with polyester cotton blend thread, due to its greater chemiluminescent sensitivity in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…The precision of the procedure using different devices was calculated at three potassium concentrations (1.26x10 -4 , 1.26x10 -3 , 4.00x10 -2 M) using 10 replicates each, obtaining a mean relative standard deviation of 1.34% (Table 1). This means a better precision compared to other thread-based procedures: Mao et al 28 found a 9.3% RSD for the biomarker squamous cell carcinoma antigen test; the procedure for DNA detection described by of Du et al 29 has a precision of 9.8%; Lu et al 31 found precisions around 5% in their enzymatic test for hydrogen peroxide and related analytes based on chemiluminescence measurement. The precision figures found here can be ascribed to the simple device used and the use of the H coordinate.…”
Section: Calibration and Analytical Parametersmentioning
confidence: 99%
“…The precision of the procedure using different devices was calculated at three potassium concentrations (1.26x10 -4 , 1.26x10 -3 , 4.00x10 -2 M) using 10 replicates each, obtaining a mean relative standard deviation of 1.34% (Table 1). This means a better precision compared to other thread-based procedures: Mao et al 28 found a 9.3% RSD for the biomarker squamous cell carcinoma antigen test; the procedure for DNA detection described by of Du et al 29 has a precision of 9.8%; Lu et al 31 found precisions around 5% in their enzymatic test for hydrogen peroxide and related analytes based on chemiluminescence measurement. The precision figures found here can be ascribed to the simple device used and the use of the H coordinate.…”
Section: Calibration and Analytical Parametersmentioning
confidence: 99%
“…The second group are based upon single threads, which generally involve much smaller solution volumes, as in these examples the flow within the strands of the thread is confined to one direction. The use of this later platform has been applied to bacteria isolation and quantification [24], chemotaxis studies for cell culture systems [25], immunoassays [26,27], blood typing [28], chemical synthesis [29], and the determination of nucleic acids [30,31], proteins [4,7,29,[31][32][33][34], glucose [29,[35][36][37], drugs [38], small ions [6,8,32,39] and metals [40]. Several detection techniques have been used for these various applications, with the most common, albeit the least sensitive, being simple colorimetric detection.…”
Section: Introductionmentioning
confidence: 99%
“…Furushima [27] replaced the traditional auxiliary pumping device with a siphon cooling device as a cooling water system of a photovoltaic model, producing an obvious result in energy conservation. Lu [28] introduced continuous siphonage flow as a renewable fluid driving force to improve the detection reproducibility for trace analytes in quantitative and sensitive assays.…”
Section: Introductionmentioning
confidence: 99%